Efektivitas Manajemen Pengawasan dalam Peningkatan Kualitas Pendidikan Pesantren di Pondok Pesantren Darul Ulum Karangpandan Rejoso Pasuruan - Mat Syaifi (Tarbawi : Jurnal Studi Pendidikan Islami, 2025)
Abstract Purpose: This study aims to analyze the effectiveness of supervisory management in improving the quality of education at Pondok Pesantren Darul Ulum Karangpandan Rejoso Pasuruan, exploring how systematic supervision contributes to educational excellence in Islamic boarding schools. Design/methodology/approach: A qualitative approach with case study design was employed, utilizing observation, in-depth interviews, and documentation. Research subjects included pesantren administrators, teachers, and students, with data analyzed through thematic analysis. Research limitations/implications: The study is limited to a three-year period (2021-2023) and focuses specifically on human resource management and educational processes rather than financial or physical resource aspects. Findings: Results indicate that systematic and continuous supervisory management significantly impacts educational quality improvement. Intensive and structured supervision enhances learning quality, student discipline, and teacher professionalism through integrated planning, implementation, evaluation, and follow-up mechanisms. Originality/value: This research contributes an effective supervisory management model for pesantren education by examining the unique hybrid approach combining traditional Islamic boarding school methods with modern management elements, applicable to similar institutions nationwide.